Thymic stromal lymphopoietin promotes asthmatic airway remodelling in human lung fibroblast cells through STAT3 signalling pathway. (27th November 2012) - Wu, Jinxiang; Liu, Fen; Zhao, Jiping; Wei, Yuping; Lv, Jinghu; Dong, FangZheng; Bi, Wenxiang; Wang, Xiaoping; Wang, Junfei; Liu, Wen; Dong, Liang; Tian, Hong
Abstract : This study aimed to identify the role and regulation of thymic stromal lymphopoietin (TSLP) in asthmatic airway remodelling. To identify the expression of TSLP, α smooth muscle actin (α‐SMA) and collagen I in bronchial tissues, bronchial biopsy specimens were collected from patients with asthma and healthy controls and stained with specific antibodies, respectively. To characterize the signalling pathways regulated by TSLP, we silenced or overexpressed TSLP in human lung fibroblast (HLF‐1) cells by shRNA approaches or transfection and detected the expression of TSLP receptor (TSLPR) by enzyme‐linked immunosorbent assay and Western blot analysis. In TSLP signalling pathway, the protein expression of total signal transducer and activator of transcription 3 (STAT3), STAT5, the phosphorylation of STAT3 (pSTAT3) and STAT5 (pSTAT5), TSLP, α‐SMA and collagen I were also detected by Western blotting. In addition, the α‐SMA, collagen I and mRNA expression were determined by real‐time reverse‐transcription. To further confirm the TSLP‐STAT3 signalling pathway in HLF‐1 cells, we inhibited STAT3 activity by targeted small molecules and then detected TSLP‐induced expression of α‐SMA and collagen I in both mRNA and protein levels by quantitative real‐time reverse‐transcription and Western blotting, respectively. First, overexpression of TSLP, α‐SMA and collagen I was detected in epithelium collected from patients with asthma. Second, STAT3 activity and the expression of α‐SMA and collagen I were controlled, regulated by TSLP. Specifically, the pSTAT3, α‐SMA and collagen I were induced by the introduction of TSLP in HLF‐1 cells, and the repression of α‐SMA and collagen I was detected after TSLP silencing. Third, no changes of pSTAT5 were found in the presence of the STAT3 inhibitor, and TSLP‐induced α‐SMA and collagen I upregulation is in a STAT3 dependent manner. If we inhibit STAT3 activity by STAT3 targeted small molecules, TSLP‐induced α‐SMA and collagen I upregulation cannot be detected. The functions of TSLP in asthmatic airway remodelling were performed through STAT3 signalling pathway. Copyright © 2012 John Wiley & Sons, Ltd.